MENINGKATKAN JOYFUL LEARNING MELALUI APLIKASI QUIZIZ PADA PEMBELAJARAN MATEMATIKA - Emi Sentiani (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
The purpose of this study is to improve Joyfull Learning through the quizizz application in mathematics learning through a systematic review of previous studies. This study is a Systematic literature review (SLR). Reference sources come from journal articles obtained from the official portal or website of the journal indexer. After getting the article, the next step is to screen the title and abstract then review the eligibility of the full text of the article and then get the selected articles. The results of this study indicate that the application of joyful learning with the quizizz application media in mathematics learning has a positive impact on students' interest in learning. Increased interest in learning also improves student learning outcomes. Learning with a joyful learning approach will also enliven the classroom atmosphere, and eliminate boredom or saturation for students.